Diagnosis of Student’s Anxiety on Undergraduate Thesis Writing at Raden Wijaya State Buddhist College - Rahmad Setyoko; Eko Siswoyo (Jurnal Pendidikan, Sains Sosial, dan Agama, 2024)
This research aims to measure the level of anxiety and analyze the factors that cause student anxiety in writing their thesis. The research was conducted at the Raden Wijaya State Buddhist College, Wonogiri, Central Java using descriptive quantitative research. The sample for this research consisted of 55 students in semester VII of the 2023/2024 academic year. The instruments used were Zung's Self-rating Anxiety Scale and questionnaires. Data were analyzed using descriptive statistics. The research results show that students' anxiety level in writing their thesis is in the medium category with an average score of 40.8. Factors that cause student anxiety include: lack of understanding of research methodology, difficulty in finding references, fear of failure and disappointing parents, and worry about the thesis trial.